The prevalence, burden and cognizance of migraine in adolescent girls - Assadi, Mitra; Zerafati, Gazelle; Dham, Bhavpreet S.; Contreras, Liz; Akbar, Umer; Zayas, Luis; Leone, Paola (Journal of Pediatric Neurology, 2012)
Migraine represents a common neurological condition, which frequently affects adolescent girls. This cross sectional study aimed to evaluate the prevalence, impact and fund of migraine knowledge among adolescent girls. Students attending randomly selected high schools were recruited into the study by signing a consent form and completing a validated survey designed for this purpose. The survey assessed the participants fund of knowledge about migraine in five domains: migraine epidemiology, symptoms, triggers, auras and treatment options. The participants were evaluated for headache characteristics according to the International Classification of Headache Disorders, 2nd edition criteria, and categorized as having definite migraine or probable migraine. Additionally, the survey evaluated headache disability by implementing the headache impact test-6, and collected information regarding the use of over-the-counter medication. In a cohort of 309 girls, 14–18 years old, 18% fulfilled the criteria for definite migraine and 25% for probable migraine, with mean headache impact test-6 scores of 62.5 and 55.2, respectively (P < 0.0001). Furthermore, the students fund of knowledge was substantially limited in regards to migraine auras and moderately limited in regards to symptoms, triggers and treatments. A significant portion of the migraineurs self-medicated using over-the-counter medications. The prevalence of migraine in late adolescent girls is very close to that of adult women. The information regarding the cognizance of migraine ought to be used as a guideline for designing educational tools for this population.
Keywords: Prevalence; migraine; adolescence; girls; burden; cognizance